KINERJA KEUANGAN DENGAN METODE EVA (ECONOMIC VALUE ADDED) PADA BPR TANJUNGPINANG (An-Nisbah: Jurnal Ekonomi Syariah, 2018)
EVA is a method of financial management to measure the economic profit in a company that states that prosperity can only be created when the company is able to meet all operating costs and capital costs. With EVA method can be known whether PT BPR Central Sejahtera Tanjungpinang happened addition to its economic value. The research method used is qualitative descriptive method. The EVA classification can be calculated from the NOPAT (Net Operating Profit After Tax) component, WACC (Weighted Average Cost of Capital) and IC (Invested Capital) contained in the financial statements of PT BPR Central Sejahtera Tanjungpinang with data from 2012 until 2017. This research reveals a positive EVA result in 2012 with an EVA of 63,515,000, in 2013 with EVA of 2,138,086,000, in 2014 with EVA of 73,105,000, in 2013 with EVA of 797,470,000 and in 2014 with an EVA value of 714.750.000. In addition to these positive results, the study also revealed negative EVA results in 2015 with an EVA value of minus 65.06 million. From the analysis results obtained conclusion that the financial performance of PT BPR Central Sejahtera Tanjungpinang quite good. PT BPR Central Sejahtera Tanjungpinang can add value to the company in 2012,2013,2014,2016 and 2017, except in 2015, PT BPR Central Sejahtera Tanjungpinang is considered failed to increase its economic value